Comparative assessment of Cranberry and Chlorhexidine mouthwash on streptococcal colonization among dental students: A randomized parallel clinical trial - Khairnar, Mahesh R. (Contemp Clin Dent, 2015)
BACKGROUND: Chlorhexidine gluconate mouthwash has earned an eponym of the gold standard against oral infections, but with certain limitations. There is no effective alternative to Chlorhexidine. Cranberry is known to inhibit bacterial adhesion in various systemic infections and acts as a strong antioxidant. However, it is less explored for its dental use. Hence, there is a need to evaluate its effect against oral infections. AIM: The aim was to compare the efficacy of 0.2% Chlorhexidine mouthwash with 0.6% Cranberry mouthwash on Streptococcus mutans. MATERIALS AND METHODS: This was a double-blind, randomized parallel group clinical trial. Total sample of 50 subjects, aged 18–20 years, were randomly divided into two groups, Group A (25) and Group B (25) were given 10 mL of Chlorhexidine mouthwash and Cranberry mouthwash twice daily, respectively, for 14 days each. The plaque samples, which were taken from the subjects on 1(st) day and 14(th) day, were inoculated on blood agar plates and incubated at 37°C for 24–48 h. Number of streptococcal colony forming units were calculated using digital colony counter. The data were subjected to paired t-test and unpaired t-test at a 5% significance level. RESULTS: (1) Chlorhexidine mouthwash showed 69% reduction whereas Cranberry mouthwash showed 68% reduction in S. mutans count. (2) No significant difference was seen between Chlorhexidine and Cranberry mouthwash on streptococci. CONCLUSION: Cranberry mouthwash is equally effective as Chlorhexidine mouthwash with beneficial local and systemic effect. Hence, it can be used effectively as an alternative to Chlorhexidine mouthwash.